1998
DOI: 10.1046/j.1365-2885.1998.00127.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the 5‐lipoxygenase inhibitor, fenleuton, on antigen‐induced neutrophil accumulation and lung function changes in horses with chronic obstructive pulmonary disease

Abstract: The leukotrienes (LT) LTD4 and LTB4 have been shown to cause bronchoconstriction and neutrophil accumulation, respectively, in horse lungs. Such changes are characteristic of the equine allergic respiratory disease, chronic obstructive pulmonary disease (COPD). To further investigate the role of these putative mediators in the pathogenesis of equine COPD the effect of a 5-lipoxygenase inhibitor, fenleuton, on antigen-induced changes in horses with this condition has been examined. Six horses with COPD underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…p Similarly, administration of a 5-LO inhibitor prior to allergen challenge in affected horses did not reduce pulmonary neutrophilia and did not significantly improve their lung function. 16 However, in the 2 horses that responded severely to the challenge, there was a marked reduction in lung function associated with drug administration. 16 While these findings indicated an overall poor therapeutic benefit of these agents for the prevention of heaves, they also suggested that LT contribute in some circumstances to the airway obstruction seen in heaves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…p Similarly, administration of a 5-LO inhibitor prior to allergen challenge in affected horses did not reduce pulmonary neutrophilia and did not significantly improve their lung function. 16 However, in the 2 horses that responded severely to the challenge, there was a marked reduction in lung function associated with drug administration. 16 While these findings indicated an overall poor therapeutic benefit of these agents for the prevention of heaves, they also suggested that LT contribute in some circumstances to the airway obstruction seen in heaves.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a 5-LO inhibitor and a FLAP antagonist in affected horses has been investigated and led to equivocal results. 16,p In a preliminary study in which a FLAP antagonist was administered to horses with heaves prior to allergen challenge, no improvement in airway function and inflammation was observed. p Similarly, administration of a 5-LO inhibitor prior to allergen challenge in affected horses did not reduce pulmonary neutrophilia and did not significantly improve their lung function.…”
Section: Discussionmentioning
confidence: 99%
“…37 Our enthusiasm for suggesting a role of LTB 4 in RAO is tempered somewhat by the observation that the 5-lipoxygenase inhibitor fenleuton did not diminish the accumulation of neutrophils in the lungs of horses with chronic obstructive pulmonary disease. 38 …”
Section: Discussionmentioning
confidence: 99%
“…Airway neutrophils are present in large numbers in the airways of horses with heaves and may contribute to the disease through the release of several inflammatory mediators. They are recruited 3–5 h following the beginning of exposure to stable dust, the process is reversible within 4 days after the cessation of a short exposure (5–7 h), 125–127 and up to 3 weeks or more under more natural conditions 79 . Resolution of airway inflammation coincides with neutrophil apoptosis and phagocytosis by alveolar macrophages 125 .…”
Section: Airway Inflammationmentioning
confidence: 99%
“…Other mediators increased during heaves exacerbation, including serotonin, endothelin‐1, histamine and leukotriene D 4 , potentiate the response of equine smooth muscle cells to acetylcholine, or increase its release. However, while they may contribute to increased cholinergic airway tone, cysteinyl leukotrienes are not believed to be major contributors to bronchospasm as leukotriene antagonists are ineffective for the treatment of heaves 127,161,191 …”
Section: Neuronal and Neuroendocrine Control Of Bronchospasmmentioning
confidence: 99%